Pemanfaatan Social Media Marketing dalam Meningkatkan Penjualan Keripik Pisang di Umkm Ayofficial Tarus Kabupaten Kupang: Perspektif Produsen dan Konsumen - Seingo, Kresensia Ivoni Stevani; Olviana, Tomycho; Siubelan, Yacobus; Mahendra, Bayu; Chamdra, Santhy (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the influence of social media marketing on the sales of banana chips produced by the MSME AYOfficial in Kupang Regency, and identifies the most effective platform. Using a quantitative approach with SmartPLS analysis on 100 respondents, the results show that TikTok, Instagram, and WhatsApp have a significant impact on sales, while Facebook does not have a significant effect. The R-square value of 0.713 indicates that social media can explain 71.3% of the variation in sales. TikTok and WhatsApp are recommended as the primary focus for the MSME's marketing strategy. TikTok Marketing (X1) exerted the most influence with a t-statistic of 2.178, a p-value of 0.029, and a Beta coefficient value (β) of 0.588. WhatsApp Marketing (X3) also had a significant effect with a t-statistic of 2.142, a p-value of 0.032, and a Beta coefficient (β) of 0.572. Instagram Marketing (X2) showed significant but smaller influence, with a t-statistic of 1.998, a p-value of 0.046, and a Beta coefficient (β) of 0.149. In contrast, Facebook Marketing (X4) had no significant effect on sales (t-statistic 1.187; p-value 0.235), (2) Overall, TikTok was the most effective social media in increasing sales, followed by WhatsApp and Instagram. The marketing strategy on TikTok as the main medium is proven to be the most influential on sales, by optimizing creative content, trends, and influencer collaborations. TikTok and WhatsApp are suggested as the main focus of marketing MSME products.